Drug survival rates and reasons for drug discontinuation in psoriasis. (November 2016) - Arnold, Tobias; Schaarschmidt, Marthe‐Lisa; Herr, Raphael; Fischer, Joachim E.; Goerdt, Sergij; Peitsch, Wiebke K.
Summary: Background and objectives: Moderate‐to‐severe psoriasis frequently requires long‐term systemic therapy. Reflecting efficacy, safety, and treatment satisfaction, drug survival is an indicator of therapeutic success. The objective of the present study was to assess drug survival rates and reasons for discontinuation of fumaric acid esters (FAE), methotrexate (MTX), acitretin (ACI), cyclosporine A (CyA), adalimumab (ADA), etanercept (ETA), infliximab (INF), and ustekinumab (UST) in patients with moderate‐to‐severe psoriasis. Patients and methods: We performed a retrospective analysis of 373 patients who had received a total of 696 treatment courses at a German university hospital in the period 1/2003–5/2014. Results: The crude probability of survival was highest for UST, followed by ADA, ETA, INF, FAE, MTX, ACI, and CyA. In multivariate regression analysis using FAE as reference, hazard ratios (HR) for discontinuation were 0.14 (95 % confidence interval: 0.06–0.35) for UST, 0.43 (0.26–0.73) for ADA, 2.11 (1.14–3.91) for ACI, and 3.26 (1.44–7.39) for CyA. INF showed longer survival when combined with MTX (HR 2.87, 1.21–6.81). Traditional systemic antipsoriatic agents as well as INF were most frequently discontinued due to adverse events; all other biologics, due to inefficacy with respect to cutaneous lesions. Conclusions: Drug survival rates should be integrated into therapeutic decisions in order to provide patients with an optimal long‐term strategy.